ANTHRAQUINONE FROM THALLUS OF LICHEN Ramalina javanica Nyl - Suyanto Suyanto; Wahyudi Priyono Suwarso; Soleh Kosela; Hery Suwito; Pratiwi Pudjiastuti; Sri Winiati; Nurdin Saidi (Indonesian Journal of Chemistry, 2006)
The isolation of 1,3,8- trihydroxy-2(1'-pentanol)-6-methoxy anthraquinone from acetone extract of lichen thallus of Ramalina javanica Nyl. was carried out. Its structure was determined based on spectroscopic evidences.